Benchmarking the charge storage mechanism in nickel cobalt sulfide nanosheets anchored on carbon nanocoils/carbon nanotubes nano-hybrid for high performance supercapacitor electrode. (10th December 2022) - Khan Abdul, Sammed; Anuj, Kumar; Amjad, Farid; Mohammad, Tabish; Muhammad, Asif; Muhammad, Usman; Akmal, Abbas; Saira, Ajmal; Lujun, Pan; Ghulam, Yasin
Abstract: To improve the capacity of electrodes for energy storage device, a promising architecture with enhanced electrochemical performance is extremely desired. Benefiting from the high conductivity and lower electronegativity of sulfur among chalcogens, transition metal sulfides are favorable contender of being used as an electrode material for supercapacitor device. Herein, three dimensional (3D) hybrid architecture composed of carbon nanocoils/nickel foam (CNCs/NF) substrate decorated with nickel cobalt sulfide (NiCoSx) nanosheets and carbon nanotubes (CNTs), has been fabricated via two step solvothermal reaction accompanied by vacuum filtration technique. CNTs act as conducting bridges between the porous nanosheets. The optimized CNTs/NiCoSx/CNCs/NF hybrid structure elucidates excellent specific capacitance of 3184 F g −1, outstanding capacitance retention (97.2 % after 3000 cycles) and significant capability rate (79 %). Furthermore, Density Functional Theory (DFT) calculations demonstrate that the significant capacitance enhancement in NiCoSx/CNCs originates from the enriched density of states near the Fermi level. The synergistic effect of NiCoSx anchored on CNCs/NF and CNTs is mainly responsible to significant electrochemical performance thereby achieves improved electron conductivity, increased ion diffusivity and efficacious redox reactions. Additionally, benefiting from the aforementioned properties, the CNTs/NiCoSx/CNCs/NF composite urges the researcher to use as a favorable contender for supercapacitor electrodes. Graphical abstract: Unlabelled Image Highlights: Carbon nanocoils(CNCs) were grown on the catalyst loaded Nickel foam (NF) by chemical vapor deposition (CVD) method. Nickel cobalt sulfide (NiCoSx ) nanosheets decorated on carbon nanocoils/nickel foam (CNCs/NF) substrate has been synthesized through two step solvothermal reaction. Well-designed, binder-free and free-standing electrode with porous architecture help to improve the diffusion kinetics. The optimized CNTs/NiCoSx/CNCs/NF hybrid structure elucidates excellent specific capacitance of 3184 F g −1 at a current density of 1 A g −1, significant capability rate (79.2 %) and outstanding capacitance retention (97.2 % after 3000 cycles).